Saturated Fats Versus Polyunsaturated Fats Versus Carbohydrates for Cardiovascular Disease Prevention and Treatment - Siri-Tarino, Patty W. (Annu Rev Nutr, 2015)
The effects of saturated fatty acids (SFAs) on cardiovascular disease (CVD) risk are modulated by the nutrients that replace them and their food matrices. Replacement of SFAs with polyunsaturated fatty acids has been associated with reduced CVD risk, although there is heterogeneity in both fatty acid categories. In contrast, replacement of SFAs with carbohydrates, particularly sugar, has been associated with no improvement or even a worsening of CVD risk, at least in part through effects on atherogenic dyslipidemia, a cluster of traits including small, dense low-density lipoprotein particles. The effects of dietary SFAs on insulin sensitivity, inflammation, vascular function, and thrombosis are less clear. There is growing evidence that SFAs in the context of dairy foods, particularly fermented dairy products, have neutral or inverse associations with CVD. Overall dietary patterns emphasizing vegetables, fish, nuts, and whole versus processed grains form the basis of heart-healthy eating and should supersede a focus on macronutrient composition.